Pengaruh Penambahan Vermikulit pada Beton Normal Terhadap Kuat Lentur Balok Terdukung Sederhana - Lintang Dian Artanti; Malik Mushthofa (Teknisia, 2023)
Concrete innovation in the construction industry continues to grow until now. One of the substantial innovations made is adding a material called vermiculite. If changes in compressive strength of concrete were observed in the previous study, then changes in concrete weight and flexural strength of concrete with the addition of vermiculite as much as 12%, 24%, and 36% were observed in this study. Concrete specimens were cured with water for 28 days and then weighted and tested for flexural strength with two loading points. The test results show that the lightest concrete is found in concrete with the addition of 36% vermiculite, with a weight difference of 0.03% lighter than normal concrete. Based on the results of the flexural strength test, the addition of 36% vermiculite makes the flexural strength of concrete 42.75% higher than normal concrete. This improvement proves that vermiculite's high water absorption properties can reduce the excess water content in concrete to reduce its weight, making the concrete denser and increasing its flexural strength.